ON ASSESSMENT OF A COMPANY'S BUSINESS REPUTATION - L. Ustinova (Russian Journal of Economics and Law)
The article actualizes the issue of the absence of a unified approach to assess a company's business reputation and its influence on the overall value of a company. The article views the main techniques of assessing intellectual property and reveals its drawbacks by the example of a chemical enterprise. The scientific novelty of the work is in the author's investigation of various factors which should by taken into account while assessing the cost of business reputation and will make the existing techniques more universal.